INDONESIAN GRADUATE STUDENTS’ CONSEQUENCES AND DECISIONS OF ENGLISH ACADEMIC WRITING INSTRUCTION (EAWI) AT HUNGARIAN UNIVERSITIES - Subandowo, Dedy; Utomo, Dhafid Wahyu (LLT Journal: A Journal on Language and Language Teaching, 2023)
This study aims to assess the consequences and decisions of EAWI for Indonesian graduate students studying in a non-native English-speaking environment. This study seeks to shape the perception of the effects of EAWI and facilitate the decision to positively impact Indonesian graduate students enrolled in higher institutions in Hungary. The study employs a semi-structured interview on educational background, English as a medium of instruction (EMI), writing assignments, self-consciousness towards English academic writing (hereafter EAW), and attitudes towards English academic writing. Four Indonesian MA and MSc students enrolled in the Faculty of Social Sciences at three different universities were involved in this study. In addition to data interpretation, the audio-recorded interview was transcribed using a Web speech API application. The extracts were subsequently translated into English, coded, and categorized into the topics chosen. The findings illustrate the consequences of English academic writing instruction on the importance of language features and grammar for students. The results involve possible impacts, experiences, perspectives, and strategies to improve the English academic writing of Indonesian graduate students. Decision ties with the university and departmental regulations and attention to principles to provide an academic writing course in English.